2020
DOI: 10.1101/2020.05.27.118851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine neurons of the VTA encode active conspecific interaction and promote social learning through social reward prediction error

Abstract: Social interactions motivate behavior in many species, facilitating learning, foraging and cooperative behavior. However, how the brain encodes the reinforcing properties of social interactions remains elusive. Here using in vivo recording in freely moving mice, we show that Dopamine (DA) neurons of the Ventral Tegmental Area (VTA) increase their activity during active interactions with unfamiliar conspecific. Using a social instrumental task, we then show that VTA DA neuron activity signals social reward pred… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Further, higher social attachment has been shown to be negatively correlated with D2R availability in humans (Caravaggio et al, 2017), indicating a potential role for DA in mediating sensitivity to social information. Additional work in other animals corroborates these associations showing that D2Rs affect prairie vole pair bonding (Wang et al, 1999) and that dopamine neurons in rats encode prediction errors that support social learning from conspecifics (Prévost-Solié et al, 2020). Together, these findings suggest that DA could differentially affect sensitivity to the perceived benefits and costs of self-control when people are in the presence of others enacting a desire.…”
Section: Introductionmentioning
confidence: 55%
“…Further, higher social attachment has been shown to be negatively correlated with D2R availability in humans (Caravaggio et al, 2017), indicating a potential role for DA in mediating sensitivity to social information. Additional work in other animals corroborates these associations showing that D2Rs affect prairie vole pair bonding (Wang et al, 1999) and that dopamine neurons in rats encode prediction errors that support social learning from conspecifics (Prévost-Solié et al, 2020). Together, these findings suggest that DA could differentially affect sensitivity to the perceived benefits and costs of self-control when people are in the presence of others enacting a desire.…”
Section: Introductionmentioning
confidence: 55%
“…The identification of pDA or pGABA VTA neurons was performed using the same approach as Prévost‐Solié et al. (2020 ) using a dataset consisting of pDA neurons, pGABA neurons, and DA neurons identified by opto tagging. Briefly, a cluster analysis with a PCA followed by an EMGM was performed on 58 electrophysiological features based on activity pattern and waveform extracted during the first 5 min of each recording.…”
Section: Methodsmentioning
confidence: 99%
“…The encoding of PEs through phasic dopaminergic activity in the midbrain has mostly been described during self-oriented learning 6 . However, a recent study in rodents showed that dopaminergic neurons in the ventral tegmental area also signal social PEs and drive social reinforcement learning using a similar mechanism 40 . We note that the sgACC also receives dense dopaminergic innervation and expresses receptors for dopamine 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, while our findings suggest that oxytocin might interact with the dopamine system to modulate the encoding of PEs, we did not pharmacologically manipulate the dopamine system in this study. This hypothesis is well informed by the known involvement of the midbrain dopaminergic neurons in encoding social PEs 40 and the engagement of midbrain dopaminergic neurons by oxytocin to encode social reward 13 , but will require further validation in human studies manipulating both systems at the same time. Third, while our dose-response model of the effects of intranasal oxytocin on the encoding of PEs in the prosocial condition suggests that the effects of intranasal oxytocin on the phasic and tonic dopamine release from midbrain neurons to the sgACC may vary by dose, BOLD fMRI does not allow to test this hypothesis directly.…”
Section: Discussionmentioning
confidence: 99%